2021
DOI: 10.1016/j.ygyno.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Gemogenovatucel-T (Vigil) maintenance immunotherapy: 3-year survival benefit in homologous recombination proficient (HRP) ovarian cancer

Abstract: Treatment options for HRP ovarian cancer are limited and associated with significant toxicity and limited clinical benefit.• Previously, Vigil has shown both safety and efficacy in the BRCA wild type, homologous recombination proficient patients.• Continued 3 year follow up has shown Vigil demonstrates durable clinical benefit to prolong OS and RFS in HRP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Moreover, ad hoc analysis of a subset of 45 patients with homologous repair proficient (HRP) tumors by Myriad MyChoice CDx (Myriad Genetics, Salt Lake City, UT) also showed improvement in RFS and OS (HR = 0.39, p = 0.007 and HR = 0.34, p = 0.019, respectively) 6 . Long term follow-up confirmed a durable survival effect 7 . Three-year survival proportion from time of procurement was 83% for Vigil and 40% for placebo ( p = 0.0006) 7 .…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Moreover, ad hoc analysis of a subset of 45 patients with homologous repair proficient (HRP) tumors by Myriad MyChoice CDx (Myriad Genetics, Salt Lake City, UT) also showed improvement in RFS and OS (HR = 0.39, p = 0.007 and HR = 0.34, p = 0.019, respectively) 6 . Long term follow-up confirmed a durable survival effect 7 . Three-year survival proportion from time of procurement was 83% for Vigil and 40% for placebo ( p = 0.0006) 7 .…”
Section: Introductionmentioning
confidence: 64%
“…Long term follow-up confirmed a durable survival effect 7 . Three-year survival proportion from time of procurement was 83% for Vigil and 40% for placebo ( p = 0.0006) 7 . A correlation of systemic immune response to Vigil clinical benefit was noted using ELISPOT assay 3 , 8 .…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…A clinical trial of an autologous tumor vaccine named gemogenovatucel-T (Vigil) (NCT02346747) has shown that Vigil provided personal neoantigens, downregulated TGF-β 1 and 2 and induced GMCSF expression, leading to systemic immunosuppressive activities. Current results have indicated long-term beneficial effects of Vigil with respect to primary endpoints and support further investigation of Vigil in ovarian cancer [ 110 ]. Studies have found that inhibiting the CXCR4/CXCL12 axis can increase sensitivity to anti-PD-1 and anti-CTLA4 immunological therapies [ 41 , 56 ].…”
Section: Therapeutic Prospective Of Cafs In Ovarian Cancermentioning
confidence: 67%